Highlights of Thirty-Year Experience of CO2 Laser Use at the Florence (Italy) Department of Dermatology - Piero Campolmi; Paolo Bonan; Giovanni Cannarozzo; Andrea Bassi; Nicola Bruscino; Meena Arunachalam; Michela Troiano; Torello Lotti; Silvia Moretti (The Scientific World Journal)
The CO2 laser has been used extensively in dermatological surgery over the past 30 years and is now recognised as the gold standard for soft tissue vaporization. Considering that the continuous wave CO2 laser delivery system and the newer “superpulsed” and scanned CO2 systems have progressively changed our practice and patient satisfaction, a long range documentation can be useful. Our experience has demonstrated that the use of CO2 laser involves a reduced healing time, an infrequent need for anaesthesia, reduced thermal damage, less bleeding, less inflammation, the possibility of intra-operative histologic and/or cytologic examination, and easy access to anatomically difficult areas. Immediate side effects have been pain, erythema, edema, typically see with older methods, using higher power. The percentage of after-treatment keloids and hypertrophic scars observed was very low (~1%) especially upon the usage of lower parameters. The recurrence of viral lesions (condylomas and warts) have been not more frequent than those due to other techniques. Tumor recurrence is minor compared with radiotherapy or surgery. This method is a valid alternative to surgery and/or diathermocoagulation for microsurgery of soft tissues. Our results are at times not consistent with those published in the literature, stressing the concept that multicentric studies that harmonization methodology and the patient selection are vital.